EFFECTS OF THE EXERCISE AND DIET PROGRAMS ON BODY MASS INDEX AND FASTING BLOOD GLUCOSE LEVEL IN OVERWEIGHT AND OBESE SUBJECTS (International Journal of Physiotherapy, 2019)
Background: Being overweight is a risk factor in developing many chronic diseases, and globally, the frequency of obesity rapidly increases. Our study aims to investigate the effects of an exercise program on Body Mass Index (BMI) and fasting blood glucose (FBG) level in overweight and obese subjects who have a diet program.Methods: 61 overweight and obese women subjects were included in this study. The subjects were randomly divided into two groups. The Control Group (CG) was included 32 women and received only a diet program. And, Experimental Group (EG) was included 29 women and received both diet and exercise program. A dietitian recorded weight, height, and BMI, and fasting blood glucose levels were recorded by blood test asking from subjects before and after program.Results: There was statistically significant decrease in BMI in both groups (p